Gastos públicos na agricultura - José Garcia Gasques (Instituto de Pesquisa Econômica Aplicada (IPEA), 2001)
– Public expenditure analysis in agriculture assumes importance due to the sheer amount of resources that are mobilized and by the contribution that is offered to the studies on the use of public resources. In 1999, Brazil has spent R7,99 billions in agriculture. This represents a seizable number vis-à-vis the situation of scarce resources destined to agriculture. Therefore, analysis on these resources is not only justifiable but necessary. The present study will be aimed at updating existing information and deepening the knowledge on the issue taking on previous studies. The period under analysis is 1980/1999. Nonetheless, some information already exists to the year 2000. The study points to two aspects as general conclusions: 1) There were marked changes in the way public expenditure in agriculture has been conducted. In some areas, such as the goods provision system (abastecimento) that represents one of the main programmes, the results of the instruments created by the government to carry out the commercialization have brought a slight reduction in public expenditures. This has been followed by a growing efficiency in the way agricultural policy is conducted; 2) The study draws attention to issues that would deserve to be further researched; notably, the difficulties to monitor and control a broad range of actions taken as part of public expenditure. Half of it is used in scattered actions over which the government has no oversight nor control. This has represented more than R4 billions in 1999.
Keywords: 330